Analisis Pemahaman Masyarakat Terhadap Sistem Pegadaian Syariah Pada Masyarakat Desa Mendalo Indah, Kecamatan Jambi Luar Kota - Rahmi Aulia; Hansen Rusliani; Eri Nofriza (JOURNAL OF SHARIA ECONOMICS, 2025)
Pegadaian Syariah is a non-bank financial institution that operates based on sharia principles through the implementation of *rahn* and *ijarah* contracts. Despite its rapid development, the level of public understanding of the Pegadaian Syariah system is still diverse. This study aims to analyze the level of public understanding of the Pegadaian Syariah system, identify factors that influence the use of Pegadaian Syariah products, and describe the educational efforts carried out by Pegadaian Syariah to the people of Mendalo Indah Village, Jambi Luar Kota District. This study uses a qualitative approach with field research. The research informants numbered 21 people selected using a *purposive sampling* technique, consisting of 10 people who had never used Pegadaian Syariah services, 10 Pegadaian Syariah customers, and 1 employee of Pegadaian Syariah UPS Aston Vila. Data were collected through interviews and documentation, then analyzed using the Miles and Huberman interactive analysis model which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation. The results indicate that the public's understanding of the Sharia Pawnshop system is quite good, but not yet fully comprehensive. The public generally understands that Sharia Pawnshops do not use interest, but they still have limited understanding of the rahn (non-interest) contract, the ijarah (non-interest) contract, and the fundamental differences between them and conventional pawnshops. Factors influencing public understanding and decisions to use Sharia Pawnshops include promotion and outreach, ease of procedures, service quality, service location, and religiosity. Sharia Pawnshops have undertaken various educational efforts through outreach, product promotion, consultations with prospective customers, and the provision of information on Sharia principles. However, the intensity of outreach still needs to be increased to improve the public's Sharia financial literacy. This study implies that improving Sharia financial literacy through ongoing education is a crucial strategy for increasing public understanding and trust in Sharia Pawnshops